A modular approach to catalytic stereoselective synthesis of chiral 1,2-diols and 1,3-diols - Sheng Xu; Yuanyuan Ping; Yinyan Su; Haoyun Guo; Aowei Luo; Wangqing Kong (Nature Communications)
Abstract Optically pure 1,2-diols and 1,3-diols are the most privileged structural motifs, widely present in natural products, pharmaceuticals and chiral auxiliaries or ligands. However, their synthesis relies on the use of toxic or expensive metal catalysts or suffer from low regioselectivity. Catalytic asymmetric synthesis of optically pure 1,n-diols from bulk chemicals in a highly stereoselective and atom-economical manner remains a formidable challenge. Here, we disclose a versatile and modular method for the synthesis of enantioenriched 1,2-diols and 1,3-diols from the high-production-volume chemicals ethane-1,2-diol (MEG) and 1,3-propanediol (PDO), respectively. The key to success is to temporarily mask the diol group as an acetonide, which imparts selectivity to the key step of C(sp3)-H functionalization. Additionally, 1,n-diols containing two stereogenic centers are also prepared through diastereoselective C(sp3)-H functionalization. The late-stage functionalization of biological active compounds and the expedient synthesis of chiral ligands and pharmaceutically relevant molecules further highlight the synthetic potential of this protocol.